1986
DOI: 10.1007/bf00199799
|View full text |Cite
|
Sign up to set email alerts
|

Refractory- and metallurgical-type chromite ores, Zambales ophiolite, Luzon, Philippines

Abstract: Abstract. The Zambales ophiolite is the major source of chromite ore in the Philippines. The chromitites are concordant cumulates and are associated with distinct chromitite-bearing sequences within the mantle peridotites. Refractory and metallurgical chromite deposits are spatially separated and related to different lithologic associations, which crystallized from different parental magmas. -Refractory chromite ores (30-44 wt% Cr203 ; 20-30 wt% A1203) are linked with the peridotite-troctolite-olivine gabbro l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Previous works have also highlighted the prevalence of podiform chromitites within the mantle peridotites of the ZOC. More specifically, it has been reported that Cr-rich podiform chromitites can be found in the Acoje block whereas Al-rich podiform chromitites are present in the Coto Block (Stoll, 1958;Hock et al, 1986). This bimodal occurrence has been attributed to differing conditions in terms of multi-stage melting, high water pressure and oxygen fugacity during the formation of the two blocks.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have also highlighted the prevalence of podiform chromitites within the mantle peridotites of the ZOC. More specifically, it has been reported that Cr-rich podiform chromitites can be found in the Acoje block whereas Al-rich podiform chromitites are present in the Coto Block (Stoll, 1958;Hock et al, 1986). This bimodal occurrence has been attributed to differing conditions in terms of multi-stage melting, high water pressure and oxygen fugacity during the formation of the two blocks.…”
Section: Geological Settingmentioning
confidence: 99%
“…The location of the Acoje and Coto blocks within the Masinloc massif is indicated by the stars. present in the Coto Block (Stoll, 1958;Hock et al, 1986). This bimodal occurrence has been attributed to differing conditions in terms of multi-stage melting, high water pressure and oxygen fugacity during the formation of the two blocks.…”
Section: Geological Settingmentioning
confidence: 99%
“…These carbonate mineral groups are common impurities of chromite ore, the major local source of the Zambales ophiolite. 37 , 38 The upsurge in K at Station 4 (0.821–2.01 mg/g), on the other hand, could be a result of runoff from rice farms that bound the floodplains at the mid- and downstream stations. The rice farming communities in the area highly depend on synthetic, inorganic fertilizers to improve their crop harvests.…”
Section: Discussionmentioning
confidence: 99%
“…Through a combination of these reactions and fractional crystallization, the melt will become saturated to supersaturated, first with respect to chromian spinel and olivine and then with respect to pyroxene. This step is seen clearly in cogenetic dikes in the mantle sections of the Oman (Ceuleneer and Nicolas, 1985), Zambales (Hock et al, 1986), and Bay of Islands (Edwards, 1990(Edwards, , 1995 ophiolites, where pyroxenite dikes formed after pods of chromitite and dikes of chromian spinel-bearing dunite.…”
Section: Melt and Peridotite Reaction And Crystallization Of Chromianmentioning
confidence: 94%